Measuring empathic, person-centred communication in primary care nurses: validity and reliability of the Consultation and Relational Empathy (CARE) Measure. Issue 1 (December 2015) - Bikker, Annemieke; Fitzpatrick, Bridie; Murphy, Douglas; Mercer, Stewart
Abstract Background Empathic patient-centred care is central to high quality health encounters. The Consultation and Relational Empathy (CARE) Measure is a patient-rated experience measure of the interpersonal quality of healthcare encounters. The measure has been extensively validated and is widely used by doctors in primary care but has not been validated in nursing. This study assessed the validity and reliability of the CARE Measure in routine nurse consultations in primary care. Methods Seventeen nurses from nine general medical practices located in three Scottish Health Boards participated in the study. Consecutive patients (aged 16 years or older) were asked to self-complete a questionnaire containing the CARE Measure immediately after their clinical encounter with the nurse. Statistical analysis included Spearman's correlation and principal component analysis (construct validity), Cronbach's alpha (internal consistency), and Generalisability theory (inter-rater reliability). Results A total of 774 patients (327 male and 447 female) completed the questionnaire. Almost three out of four patients (73 %) felt that the CARE Measure items were very important to their current consultation. The number of 'not applicable' responses and missing values were low overall (5.7 and 1.6 % respectively). The mean CARE Measure score in the consultations was 45.9 and 48 % achieved the maximum possible score of 50. CARE Measure scores correlated in predicted ways with overall satisfaction and patient enablement in support of convergent and divergent validity. Factor analysis found that the CARE Measure items loaded highly onto a single factor. The measure showed high internal consistency (Cronbach's alpha coefficient = 0.97) and acceptable inter-rater reliability (G = 0.6 with 60 patients ratings per nurse). The scores were not affected by patients' age, gender, self-perceived overall health, living arrangements, employment status or language spoken at home. Conclusions The CARE Measure has high face and construct validity, and internal reliability in nurse consultations in primary care. Its ability to discriminate between nurses is sufficient for educational and quality improvement purposes.